Tolterodine Treatment Improves Storage Symptoms Suggestive of Overactive Bladder in Men Treated With α-Blockers - Chapple, Christopher; Herschorn, Sender; Abrams, Paul; Sun, Franklin; Brodsky, Marina; Guan, Zhonghong (European urology, 2009)
Some men receiving α-blocker therapy for lower urinary tract symptoms report persistent storage symptoms suggestive of overactive bladder (OAB). To evaluate the efficacy of tolterodine extended release (ER) in men on α-blocker therapy. This double-blind trial included men aged ≥40 yr with frequency, urgency, and at least moderate problems reported on the Patient Perception of Bladder Condition (PPBC), despite being on a stable dose of α-blocker for ≥1 mo. Subjects were randomized to tolterodine ER 4mg per day or placebo for 12 wk while continuing their prescribed α-blocker therapy. At baseline and week 12, subjects completed the PPBC, International Prostate Symptom Score (IPSS), Overactive Bladder Questionnaire (OAB-q), and 5-d bladder diaries using the five-point Urinary Sensation Scale (USS). Frequency–urgency sum was defined as the sum of USS ratings for all micturitions. PPBC improvement from baseline to week 12 was reported by 63.6% and 61.6% of subjects receiving tolterodine ER plus α-blocker and placebo plus α-blocker, respectively; this treatment difference, which was the primary end point, was not statistically significant (p>0.6699). At week 12, subjects receiving tolterodine ER plus α-blocker had significantly greater improvements versus placebo plus α-blocker in 24-h micturitions (−1.8 vs −1.2; p=0.0079) and daytime micturitions (−1.3 vs −0.8; p=0.0123); 24-h urgency episodes (−2.9 vs −1.8; p=0.0010), daytime urgency episodes (−2.2 vs −1.4; p=0.0017), and nocturnal urgency episodes (−0.5 vs −0.3; p=0.0378); frequency–urgency sum (−7.8 vs −5.1; p=0.0065); IPSS storage subscale (−2.6 vs −2.1; p=0.0370); and OAB-q symptom bother scale (−17.9 vs −14.4; p=0.0086) and coping domain (15.4 vs 12.4; p=0.0491). Acute urinary retention requiring catheterization occurred in <1% of either group. There were no clinically meaningful changes in postvoid residual volume or maximum urinary flow rate. Men with bothersome OAB symptoms despite continued α-blocker therapy showed significantly greater improvements in diary variables, IPSS Storage scores, and symptom bother when receiving additional tolterodine ER versus placebo plus α-blocker. Men who experience storage symptoms suggestive of overactive bladder despite α-blocker therapy for their lower urinary tract symptoms may benefit from the addition of tolterodine extended release to their α-blocker therapy.